PEMANFAATAN EKSTRAK KULIT NENAS (Ananas comosus L. Merr) DALAM MENINGKATKAN KUALITAS DAGING AYAM PETELUR AFKIR - ENDAH PURNAMASARI '; ALHAMI ELTHA '; DEWI FEBRINA '; EVI IRAWATI ' (Universitas Riau, 2014)
After 2 years producing eggs, a layer hen is considered not productive anymore, and usually exploited as analternative source of chicken meat, other than natural broiler chicken. However, the texture and quality ofthe meat is less favorable compared to the broiler meat, in terms of its tenderness and nutritional values, eg.protein, fat, and its ash contents. Marinating the meat with pineapple’s skin extract (which containedpineapple’s bromelain enzyme) was considered would improve the meat tenderness. This study was aimed tomeasure the levels of protein, fat, ash, water, and pH of the ex layer hens’ meat marinated in pineapple skinextracts with different concentrations. The Completely Randomized Design (CRD) with 5 treatments and 4replications were applied to the experiment. The treatment was comprised of 5 level of concentration of skinextract of pineapple, i.e. 0%, 25%, 50%, 75%, and 100% w/v. The meat was marinated for 30 minutes.Variables measured were pH, moisture content, protein content, ash content, and fat content. Differencesbetween treatments then analyzed further with Duncan’s Multiple Range Test (DMRT). The result showedthat marinating the ex layer chicken breast’s in the skin extracts of pineapple 100% w/v gave a very significantdifference in improving to the highest protein content, while the water content and pH levels of the meatshowed the lowest value.Key words : ex laying chicken’s meat, pineapple-skin’s extract, bromelain, meat’s texture